Partisan polarization and US foreign policy: Is the centre dead or holding?. Issue 5 (September 2016) - Hurst, Steven; Wroe, Andrew
Abstract Scholars generally agree that most congressional decision-making behaviour has become characterized by partisan polarization. One area to which this consensus does not extend, however, is decision-making on foreign and national security issues. While a majority of scholars believe congressional foreign policy voting is now polarized, others insist that bipartisanship remains the norm. Examining roll-call votes in the House of Representatives from 1970 to 2012, this paper brings three new elements to bear on the dispute. Using a more comprehensive range of indicators, we re-examine the longitudinal data previously presented by scholars; we add an analysis of the roll-call data for the 2004–2013 period, and we utilize a static measure of polarization. Our analysis of the data reveals a cyclical trend of increasing and decreasing polarization and we conclude that it is too simplistic to characterize congressional voting on foreign and national security issues since 1970 as either partisan or bipartisan.